The Influence of Training on Competence at PT.Amanah Putra Pratama (Case Study on the Distribution of Indonesian Workers to Abroad) - Agung Surya Dwianto; Pupung Purnamasari; Taufik Aulia (JURNAL EKUIVALENSI, 2018)
This study aims to examine the effect of training on the competence of Indonesian workers in PT Amanah Putra Pratama. The study was conducted at PT Amanah Putra Pratama by using a research sample of 38 Indonesian workers counted in July 2018 because at that time research was being carried out, while every month the number of Indonesian workers in PT.Amanah Putra Pratama was uncertain. Data collection was carried out by distributing research instruments, namely questionnaires containing questions to measure training and competence. The collected data is then processed using simple linear regression analysis with the help of SPSS version 16.0 software. Research also shows that there is a positive and significant influence given by training that has a strong influence in influencing the creation of better competencies in PT Amanah Putra Pratama optimally, the R value (correlation) produced is 0.514, it can be said that training and competence positively related by 51.4%. While the coefficient of determination R2 (R Square) is 0.265, which means that the ability of the training variable to influence competence in PT Amanah Putra Pratama is 26.5%, while 73.5% is the contribution of other factors not observed in this study. Keywords: Training, Competence